PENYULUHAN HAK WARGA NEGARA ATAS BANTUAN HUKUM - Pahlawan MP, Muhamad Rezky; Chadijah, Siti; Wardhani, Dwi Kusumo; Ekawati, Dian; Ngatiran, Ngatiran (LPPM Universitas Pamulang, 2020)
Legal aid is an effort to fulfill the human rights, especially of the poorest groups of the society. The Constitution guarantees the right of every citizen to equal treatment before the law, including the right to access justice through legal aid. Based on the principle of equality before the law and the purpose of access to law and justice, the Government of Indonesia issued a regulation to realize these principles and objectives through Law No. 16 of 2011 on Legal Aid. The substance of the regulation requires law enforcers especially advocates as legal aid providers to provide legal assistance free of charge to the poor in Indonesia, moreover these obligations are normative obligations for advocates as officium nobile (noble profession) and the mandate of the Law No.18 of 2003 concerning Advocates. It is expected that efforts to provide free legal assistance can do optimal and effective in serving the underprivileged.